Black opera : history, power, engagement - André, Naomi Adele (University of Illinois Press, 2018)
From classic films like Carmen Jones to contemporary works like The Diary of Sally Hemings and U-Carmen eKhayelitsa, American and South African artists and composers have used opera to reclaim black people's place in history. The author draws on the experiences of performers and audiences to explore this music's resonance with listeners in the twenty-first century. Interacting with creators and performers, as well as with the works themselves, the author reveals how Black opera unearths suppressed truths. These truths provoke complex, if uncomfortable, reconsideration of racial, gender, sexual, and other oppressive ideologies. Opera, in turn, operates as a cultural and political force that employs an immense, transformative power to represent - or even liberate.--description from publisher's website.